Сhaotic magnetoconvection in a non-uniformly rotating electroconductive fluids - Kopp, M.I.; Tur, A.V.; Yanovsky, V.V. (Вопросы атомной науки и техники, 2018)
We study a new type of magnetoconvection in a nonuniform rotating plasma layer under a constant vertical magnetic field. To describe the weakly nonlinear stage of convection we apply Galerkin-truncated approximation and we obtain the system of equations of Lorentz type. A numerical analysis of these equations shows the presence of chaotic behavior of convective flows. Criteria for the appearance of chaotic motions are found depending on the convection parameters (Rayleigh number Ra ), magnetic field (Chandrasekhar number Q ), rotation (Taylor number Ta ) for the Keplerian angular velocity profile (Ro = −3/4) of the medium.